2019
DOI: 10.1002/jbmr.3917
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Alcohol Intake but Not Muscle Strength in Young Men Increase Fracture Risk at Middle Age: A Cohort Study Linked to the Swedish National Patient Registry

Abstract: We aimed to determine the relationship between handgrip strength, smoking, and alcohol consumption in young men and fracture risk at middle age. Thus, we carried out a cohort study including young men undergoing conscription examination in Sweden from September 1969 to May 1970 at a typical age of 18 years. Data on muscle strength, height, weight, and lifestyle factors were linked to the National Patient Register 1987–2010. Handgrip strength was considered the main exposure and smoking and alcohol consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…We identified 18 population-based prospective cohort studies reporting on the associations between handgrip strength and fracture risk (Electronic Supplementary Material 7 and Table 3 ). [ 2 , 3 , 15 , 20 , 27 , 28 , 31 , 36 , 38 , 54 , 60 , 62 65 , 70 , 74 ] Including the current study, the pooled analysis comprised 19 studies involving 220,757 participants and 9199 incident fractures (comprising 1302 hip fractures). Average age of participants ranged from 18 to 81 years with a weighted mean (SD) of 48 (16) years.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 18 population-based prospective cohort studies reporting on the associations between handgrip strength and fracture risk (Electronic Supplementary Material 7 and Table 3 ). [ 2 , 3 , 15 , 20 , 27 , 28 , 31 , 36 , 38 , 54 , 60 , 62 65 , 70 , 74 ] Including the current study, the pooled analysis comprised 19 studies involving 220,757 participants and 9199 incident fractures (comprising 1302 hip fractures). Average age of participants ranged from 18 to 81 years with a weighted mean (SD) of 48 (16) years.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a multidisciplinary team, including physiotherapists and exercise physiologists, may aid in reducing fracture risk in patients with schizophrenia [ 48 ]. Furthermore, smoking and alcohol use are common in patients with schizophrenia, both of which are established risk factors for osteoporosis and osteoporotic fracture [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…And Hoge et al (34) showed that higher income was associated with better physical functioning in several areas relative to PIR. Relevant human (35,36) and animal (37,38) studies have demonstrated significant negative effects of smoking and alcohol consumption on muscle composition and strength. Scientific physical activity has been shown to improve human health and muscle strength levels (36,39,40), but sedentary time has a range of adverse physiological effects on muscle strength independent of physical activity (41-43).…”
Section: Nhanesmentioning
confidence: 99%
“…Relevant human (35,36) and animal (37,38) studies have demonstrated significant negative effects of smoking and alcohol consumption on muscle composition and strength. Scientific physical activity has been shown to improve human health and muscle strength levels (36,39,40), but sedentary time has a range of adverse physiological effects on muscle strength independent of physical activity (41-43). Previous studies have confirmed that hypertension (44,45), hyperlipidemia (46)(47)(48) Smoking conditions are divided into three categories: never (smoked less than 100 cigarettes in life), former (smoked more than 100 cigarettes in life and smoke not at all now), now (smoked moth than 100 cigarettes in life and smoke some days or every day).…”
Section: Nhanesmentioning
confidence: 99%